THE USE OF VOA (VOICE OF AMERICA) LEARNING ENGLISH TO IMPROVE STUDENTS’ SPEAKING SKILL - Afrida Rini Fitriwati; Siti Asriati; Ratu Yulianti Natsir (FKIP Unismuh Makassar, 2022)
This research aimed to find out whether or not the use of VOA (Voice of America) Learning English improve the students’ speaking skill in terms of accuracy and fluency at tenth grade students of SMK Negeri 1 Pinrang. The researcher used pre-experimental design with one group pre-test post-test design. The researcher conducted pre-test, treatment and post-test in the total of six meetings. The sample was class X OTKP 2 (Otomatisasi dan Tata Kelola Perkantoran) which consisted of 19 students. The instrument of this research was speaking test.The result of the research showed that there was an improvement between pre-test and post-test. The mean score of post-test in accuracy (68.78) was higher than the mean score of pre-test (51.52). Thus, the improvement of students’ accuracy was 33.50%. Moreover, the mean score of post-test in fluency (70.52) was higher than the mean score of pre-test (53.31). Thus, the improvement of students’ fluency was 32.28%. Moreover, based on the data analysis, the t-test value of accuracy was higher than the t-table value (18.55>2.101) and the t-test value of fluency was also higher than t-table (19.55>2.101). It means the Null hypothesis (H0) was rejected and Alternative Hypothesis (H1) was accepted. Therefore, the researcher concluded that the use of VOA (Voice of America) Learning English can improve students’ speaking skill at tenth grade students of SMK Negeri 1 Pinrang.